Evaluating the governmental health expenditure pattern and its association with health outcomes in Egyptian governorates - Abass, Wessam (AUC Knowledge Fountain, 2016)
Health is one of the basic human rights; not all citizens are able to access quality healthcare services; therefore, countries allocate a considerable fund to healthcare provision but there is no general agreement about the effectiveness of monetary health inputs against health outcomes. The thesis evaluates the current governmental health expenditure pattern in Egyptian governorates and its relation to selected health outcomes. The study conducts secondary analysis for grouped data from different sources for year 2013-2014, applying descriptive, correlation and regression analysis by SPSS tool. It was found that there are disparities between governorates and regions in socioeconomic, health conditions, health expenditure and health outcomes. Upper Egypt region suffers more than other regions, there is an association between government health expenditure and health outcomes but the current expenditure pattern does not improve the health outcome. Health financing system in Egypt is suffering from inefficiencies and inequalities. The thesis concludes that public resources reallocation is a key solution to solve health inequity problem. It is recommended that a resource allocation formula should be adopted by MoHP to ensure equitable allocation of resources between governorates. Poverty is the main factor affects health outcomes and several living conditions, thus there should be tailored healthcare programs targeting the poor.